Environmental risk perception and adaptation in coastal zones: the case of Long Island - Modesto, Francine (2014)
The objective of this paper is to verify which population groups are exposed to environmental risks in the municipality of Ilha Comprida, located in the southern coast of São Paulo, especially considering the hazards arising from coastal erosion that occurs in the northern part of the island. The methodology used was, first, the construction of a conceptual framework through literature review on the topic of environmental risks, vulnerability and adaptation. Second step was the use of quantitative methods for data analysis Censuses (2000 and 2010) and conducting qualitative interviews, using semi-structured questionnaires. The interviews with the resident population took into account the location of residence (according to the distance from the shore line), perception of environmental problems and hazards of the island, strategies to deal with these hazards and the perception of responsibility of public authorities in cases of disaster occurrence. The study of environmental perception of hazards and socio- demographic vulnerability of this population are key elements for understanding the involvement of people with the place and their coping strategies to deal with the environmental hazards of the municipality. The qualitative research showed that some residents relate environmental changes of the tip of the island (also) to climate change, and generally everyone knows the Mar Pequeno (a local sea channel) interference in the beach erosion phenomenon. Other environmental problems were expressed by residents regarding them as more serious than erosion, as these affect the entire population of the municipality, such as the pollution of the river Candapuí, lack of sanitation and sewage, jam of cars on unpaved streets and problems with garbage collection. Coping strategies of environmental problems that residents experience in the north of the island are individual and not collective. No joint actions, for example, between residents and vacationers occur, since the bond with them the place is different. This hampers a wider and more effective solution by local government to address the environmental problems of the municipality.